PKM Peningkatan Kemampuan Digitalisasi Kelompok PKK Desa Jabungsisir dengan Sistem Informasi Ulem-Ulem Berbasis Android - Abdul Karim; Sofyan Hajar Hamzah; Abd. Rohim (Universitas Nurul Jadid, 2022)
Abstract: Technological developments that continue to increase sharply from year to year are actually carried out in order to keep pace with the growing human need for technology. In every aspect of life, there is always digital technology that helps us every day, making activities more efficient. So far, ulem-ulem notes are usually recorded on a book or paper consisting of several adjusted columns which are not usefully efficient. The method used in this service is training in which the community is trained so that they are able to take advantage of the application of the Ulem-Ulem information system. The purpose of this service is to improve the ability of the PKK Jabungsisir Paiton Probolinggo group in utilizing digital devices, one of which is by changing the habit of storing ulem-ulem notes into digital form. Keywords: digitalization, information system, ulem-ulem